The Implementation Of Project-Based Learning And Its Impact On Student Achievement - Nur Efendi (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
: This study aims to explore the implementation of Project-Based Learning (PjBL) and its impact on student achievement at MA Darunnajah Trenggalek. In response to the growing need for more active and student-centered learning, PjBL is introduced as an alternative method that encourages students to engage in real-life problem solving and collaborative activities. The research uses a qualitative descriptive approach involving classroom observation, interviews with teachers and students, and analysis of learning documents and assessment records. The results show that PjBL significantly improves student engagement, motivation, and understanding of the subject matter. Students participating in project-based activities demonstrated better academic performance compared to their previous achievements using traditional instructional methods. Through tasks such as group presentations, research projects, and real-world applications, students developed essential skills including critical thinking, communication, and teamwork. Teachers reported a noticeable shift in classroom dynamics, where students became more proactive, enthusiastic, and responsible for their own learning. Despite some challenges such as time management and the need for careful planning, both teachers and students viewed the PjBL method positively. The findings suggest that implementing PjBL not only enhances students’ cognitive achievement but also supports character development and active participation in the learning process. This study concludes that PjBL is an effective instructional strategy for improving academic outcomes and recommends its wider application in various educational settings, particularly in Islamic senior high schools that aim to integrate academic excellence with meaningful learning experiences.